National Interethnic Women’s Network for Environmental Defense. Territorial network mapping: A methodological guide - Gonzalez, Carlos Eduardo; Salas Betancourt, Daniela; Urbano Castano, Angelica; Howland, Fanny (2024)
This methodological guide is a participatory tool that allows those who use it to map their territorial network related to one or several themes. This guide is intended for men or women producers and/or territorial leaders.